Performance of prestressed homogeneous steel I-beam and I-beam strengthened in compression - Ravindra, Vipparthy; Raju, Ponnada Markandeya (Journal of Structural Engineering, 2024)
In spite of having many advantages over prestressed concrete, prestressed steel has not been popular in academics as well as in industry. This paper is to develop an algorithm for evaluating the performance of prestressed symmetric and unsymmetric steel I-beams. For each of the rolled steel beam sections available in IS – Hand Book 1 and for spans varying from 8m to 16m, iterative calculations involved in analysis have been performed with the help of a program developed by the authors for analysis of prestressed steel beams. The output is in the form of design table giving values of dimensional design parameters like prestressing force, eccentricity, load carrying capacity and some non-dimensional parameters like force factor, eccentricity ratio percentage increase in the load carrying capacity etc. Performance of I-section and compound girder formed by welding a plate to the top flange of an I-section are considered for comparison. A straight tendon configuration over the whole span is considered for study. The study of graphs developed from the design tables revealed that the range of eccentricity that can be provided for I-section is less than that for I-section strengthened in compression by welding a plate. The maximum decrease in net deflection for I-section is 41.94 % and for I-section strengthened in compression by welding a plate is 24.04 %. Also, the maximum increase in load carrying capacity is 7.78 % for I-section and 57.08 % for I-section strengthened in compression.